The formation of corn yield capacity depending on hybrids’ choice under the conditions of unstable moistening - Marenych, М.; Kuriacha, K. (Scientific Progress & Innovations, 2025)
The analysis of hybrids’ yield capacity showed that they can conventionally be divided into those, which react on seeding rate and those ones, which have weak reaction. The following hybrids responded positively to increasing the seeding rate up to 85 thou/ha: EC Sirius, EC Paroles, Mas 23.K, Mas 30.K, DKC 3795, DKC 3472, DKC 4964, P7709, PR39H32, however in the majority of variants, the increase in the seeding rate up to 85 thou/ha resulted in yield decrease. The reaction of the following hybrids should be especially mentioned: EC Method, Mas 33.A, Mas 37.V, DKC 4014, DKC 3511, DKC 4408, and P9175, which lowered yield capacity not so sharply under the effect of the sowing rate increase. The decrease in the sowing rate also led to the considerable yield capacity lowering in several hybrids. Special attention should be paid to Mas 37.V, DKC 3509, DKC 3795, DKC 4014, PR39H32, and P9175.In case of the seeding rate decrease, in some hybrids, the indicator of yield capacity grew, which is especially noticeable in such hybrids as EC Method, Mas 30.K, DKC 3472, DKC 4964, and PR39B76. The main precondition for obtaining stable corn yields is choosing hybrids for cultivation. Under the conditions of unstable moistening, the following hybrids can form the yields of more than 10 t/ha: DKC 4964 (10.96 t/ha), DKC 4490 (10.81 t/ha), Mas 30.K (10.73 t/ha), ЕС Sensor (10.69 t/ha), P9241 (10.43 t/ha), DKC 3509 (10.16 t/гha), and ЕС Concord (10.05 t/ha). The seeding rate of 75 thou/ha turned out to be the optimal one, which enabled to form the yield capacity of DKC 4014 and P9241 hybrids of more than 11 t/ha. For DKC 4964 and ЕС Sensor hybrids, the seeding rate of 65 thou/ha turned out to be the optimal one, which enabled to receive the yields of 11.2 t/ha. The reliable criterion for selecting hybrids is also their characteristics according to FAO – it was determined that corn hybrids having the value of 370 formed the highest yields. However, taking into account the unpredictable conditions, it is expedient to expand this interval to 310–370, also paying attention to the hybrids’ genetic peculiarities, as some of mid-ripening varieties may have lower yield capacity. In particular, DKC 4964 (FAO 380) had the yield capacity of 10.96 t/ha in case of the sowing rate, while Mas 44.A yielded only 8.33 t/ha.